2014
DOI: 10.1093/gji/ggu418
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric mantle heterogeneities beneath the Zagros Mountains and the Iranian Plateau: a petrological-geophysical study

Abstract: S U M M A R YWe apply a combined geophysical-petrological methodology in order to study the thermal, compositional, density and seismological structure of the crust and upper mantle along two transects across the Arabia-Eurasia collision region. Results on the crustal thickness show minimum values beneath the Arabia Platform and Central Iran (42-43 km), and maximum values beneath the Sanandaj Sirjan zone (SSZ; 55-63 km), in agreement with seismic data. Major discrepancies in Moho depth from those derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“…Large variations of the lithospheric thickness are also suggested from the combined modelling of Bouguer anomalies and geoid height (Jimenez-Munt et al 2012). This analysis has been augmented recently with additional constraints from body-wave tomographic results and petro-physical modelling (Tunini et al 2015). These authors found evidence for important lateral variations of the composition of the lithospheric mantle suggesting variations of the buoyancy of the lithosphere.…”
Section: Introductionmentioning
confidence: 85%
“…Large variations of the lithospheric thickness are also suggested from the combined modelling of Bouguer anomalies and geoid height (Jimenez-Munt et al 2012). This analysis has been augmented recently with additional constraints from body-wave tomographic results and petro-physical modelling (Tunini et al 2015). These authors found evidence for important lateral variations of the composition of the lithospheric mantle suggesting variations of the buoyancy of the lithosphere.…”
Section: Introductionmentioning
confidence: 85%
“…Consequently, the density within the lithospheric mantle decreases with depth according to the thermal expansion coefficient and therefore, the LAB cannot be effectively constrained by seismic or petrological models. Nevertheless, although the absolute LAB-depth values can differ from a geophysical-petrological approach, the main trends will be comparable as far as the predominant effect on lateral density variations is related to temperature rather than to pressure and/or composition (see Tunini et al, 2014 for a thorough discussion). We must finally note that our methodology is also subjected to uncertainties in the determination of the depth to the geotherm defining the LAB of the order of ±10-15% (Afonso et al, 2013a,b).…”
Section: Lab Topographymentioning
confidence: 99%
“…The model shows that crustal thickening extends hundreds to thousand kilometers away from the collisional front, indicating transmission of tectonic stresses, and revealing the presence of stiff lithospheric blocks that remain almost undeformed within the collisional systems (central Iran, Tarim basin). The front of the Zagros Mountains is characterized by ~200 km thick lithosphere, and the internal regions of Anatolia, central Iran, Alborz, and Lut block by a 100–130 km thick lithosphere, in agreement with previous studies (Jiménez‐Munt et al, ; Molinaro, Zeyen, & Laurencin, ; Motavalli‐Anbaran et al, ; Tunini et al, ).…”
Section: Model Setupmentioning
confidence: 99%
“…The lithosphere strength is calculated from the lithosphere structure and the associated thermal regime. We use the recent crustal and lithospheric structure model by Robert et al (2015) and the results from Jiménez-Munt et al (2008) and Tunini et al (2015 and2016). The thin-sheet approach has proven to be useful for studying both the present-day (neotectonic) deformation in collisional settings (Barba et al, 2010;Bird, Liu, & Rucker, 2008;Cunha et al, 2012;England & Molnar, 1997;Howe & Bird, 2010;Jiménez-Munt et al, 2001Liu & Bird, 2002;Marotta et al, 2001;Negredo et al, 2002;Negredo, Jiménez-Munt, & Villaseñor, 2004;Neres et al, 2016) and its evolution through time (England & Housemann, 1989;Garcia-Castellanos & Jiménez-Munt, 2015;Jiménez-Munt, Garcia-Castellanos, & Fernandez, 2005;Jiménez-Munt & Platt, 2006;Robl & Stüwe, 2005;Sobouti & Arkani-Hamed, 1996;Sternai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%